Under the Banner Dakwah: the Radical Potential among Muslim Students in Riau - Hitami, Munzir; Bakar, Abu; Rosidi, Imron; Hanafi, Imam (LPPM IAIN Kudus, 2020)
This study is based on the presence of spirit (ghirah) to return to Islamic teachings among Muslim students in Riau after the 212. This study shows that: First, the ulama who has the same understanding with students is Habbib Rizieq Shihab. Second, the idea about Khilafah Islamiyah and the implementation of syari’ah or Islamis law is still dominant. Third, there is an idea that killing is a part of jihad. Fourth, the consciousness about differences is still low. Based on this finding, the radical potential which is high among students is basically disquieting. Furthermore, the basis of this understanding is affected by the dakwah concept of some extra campus organizations and their ideological organization.